A New Class of 1‐Aryl‐5, 6‐dihydropyrrolo[2, 1‐a]isoquinoline Derivatives as Reversers of P‐Glycoprotein‐Mediated Multidrug Resistance in Tumor Cells. (4th July 2018) - Nevskaya, Alisa A.; Matveeva, Maria D.; Borisova, Tatiana N.; Niso, Mauro; Colabufo, Nicola A.; Boccarelli, Angelina; Purgatorio, Rosa; de Candia, Modesto; Cellamare, Saverio; Voskressensky, Leonid G.; Altomare, Cosimo D.
Abstract: A number of aza‐heterocyclic compounds, which share the 5, 6‐dihydropyrrolo[2, 1‐ a ]isoquinoline (DHPIQ) scaffold with members of the lamellarin alkaloid family, were synthesized and evaluated for their ability to reverse in vitro multidrug resistance in cancer cells through inhibition of P‐glycoprotein (P‐gp) and/or multidrug‐resistance‐associated protein 1. Most of the investigated DHPIQ compounds proved to be selective P‐gp modulators, and the most potent modulator, 8, 9‐diethoxy‐1‐(3, 4‐diethoxyphenyl)‐3‐(furan‐2‐yl)‐5, 6‐dihydropyrrolo[2, 1‐ a ]isoquinoline‐2‐carbaldehyde, attained sub‐micromolar inhibitory potency (IC50 : 0.19 μm ). Schiff bases prepared by the condensation of some 1‐aryl‐DHPIQ aldehydes with p ‐aminophenol also proved to be of some interest, and one of them, 4‐((1‐(4‐fluorophenyl)‐5, 6‐dihydro‐8, 9‐dimethoxypyrrolo[2, 1‐ a ]isoquinolin‐2‐yl)methyleneamino)phenol, had an IC50 value of 1.01 μm . In drug combination assays in multidrug‐resistant cells, some DHPIQ compounds, at nontoxic concentrations, significantly increased the cytotoxicity of doxorubicin in a concentration‐dependent manner. Studies of structure–activity relationships and investigation of the chemical stability of Schiff bases provided physicochemical information useful for molecular optimization of lamellarin‐like cytotoxic drugs active toward chemoresistant tumors as well as nontoxic reversers of P‐gp‐mediated multidrug resistance in tumor cells. Abstract : Fight the resistance : Newly synthesized analogues of marine alkaloids have been discovered as reversers of multidrug resistance in cancer cells. Among them, some aldehyde derivatives (e.g., 3 ) and Schiff bases (such as 15 ) were found to be potent in vitro inhibitors of the P‐glycoprotein and/or multidrug‐resistance‐associated protein 1 efflux pumps, showing effectiveness in increasing the activity of doxorubicin in chemoresistant cancer cells.